CO2 emission of the soil on barley stubble - Szőllősi, Nikolett; Kovács, Györgyi; Zsembeli, József (Acta Agraria Debreceniensis, 2009)
In the last decades the physical and biological status of the soils in Hungary significantly decreased. The degree and intensity of CO2-production of the soil is in close correlation to its structural status and organic matter content. In a complex soil tillage experiment at Karcag in situ measurements have been carried out since 2002 in order to determine the CO2-emission of the soil. Carbon-dioxide emission of the soil in the cases of conventional tillage and reduced cultivation system was analysed in a long-term cultivation experiment. The measurements were carried out after the harvest of the barley, thus root respiration was excluded. For the spatial delimitation of the measuring area a newly developed frame+bowl set was used. Based on measurements, significant differences between cultivation systems can be recognized due to the soil structure changes and its effects